Evaluation of efficiency and mass transfer in a pulsed packed extraction column (Research, Society and Development, 2020)
Liquid-liquid extraction, or solvent extraction, is a unitary operation designed to separate one or more components from the insertion of a liquid phase that has more affinity with the components of interest. It is a technique used in various industrial process including the food industry, petrochemical and biochemical. Thus, the present work aims to investigate the operational parameters in the performance of a pulsed packed extraction column. The packed used in the extractor ir Raschig’s rings. For this, 30 runs were performed with aqueous acetic acid solution (solute) and 1-butanol solution (solvent) in order to obtain concentration data in the extract and raffinate and with these data to calculate column efficiency and mass transfer coefficient. The Murphree (1925) and Kawase (1990) models were used to calculate the efficiency. The two models chosen for the efficiency calculation presented consistent values. For the calculation of the mass transfer coefficient, six different models were used: Plug Flow Model (PFM), Safari et al. (2012), Kister (1992), Torab-Mostaedi and Safdari (2009b), Diffusion Model and GhaffariTooran et al. (2009). Among these models, two did not present coherent values: Torab-Mostaedi and Safdari (2009b) and GhaffariTooran et al. (2009). With the analysis of the results it was noted that for both efficiency and mass transfer coefficient there was a positive influence. The flow ratio was the one that most influenced column efficiency, with a percentage increase of 33.57%. Finally, an empirical model was developed to correlate column efficiency with operational parameters. The equation showed good agreement with the Murphree equation, presenting an average deviation of 7.35% which is a relatively low deviation. Thus it was possible to verify the usefulness of the packed insertions and pulsation in the extractor as a way to improve the mass transfer.